Zen and electrochemical surface finishing of materials. (4th March 2021) - Walsh, Frank C.
ABSTRACT: Zen philosophy is loosely applied to electrochemical cells used in surface finishing. The importance of considering the overall cell in a balanced, holistic fashion, rather than one reaction at a single electrode, is stressed. The electrochemical cell has six essential components, namely, a cathode, an anode, the electrolyte, the external electrical circuit, a cathodic reactant and an anodic reactant. The importance of electrochemistry in clean processing, chemical synthesis, environmental remediation and pollution sensing is considered. It remains important to adopt a broad perspective to electrodeposition processes and integrate technological progress and sustainability in the light of recent environmental restrictions and regulations.